Screening of reference genes using real-time quantitative PCR for gene expression studies in Neoseiulus barkeri Hughes (Acari: Phytoseiidae). Issue 4 (29th October 2018) - Wang, C.; Yang, J.; Pan, Q.; Yu, S.; Luo, R.; Liu, H.; Li, H.; Cong, L.; Ran, C.
Abstract: A stable reference gene is a key prerequisite for accurate assessment of gene expression. At present, the real-time reverse transcriptase quantitative polymerase chain reaction has been widely used in the analysis of gene expression in a variety of organisms. Neoseiulus barkeri Hughes (Acari: Phytoseiidae) is a major predator of mites on many important economically crops. Until now, however, there are no reports evaluating the stability of reference genes in this species. In view of this, we used GeNorm, NormFinder, BestKeeper, and RefFinder software tools to evaluate the expression stability of 11 candidate reference genes in developmental stages and under various abiotic stresses. According to our results, β -ACT and Hsp40 were the top two stable reference genes in developmental stages. The Hsp60 and Hsp90 were the most stable reference genes in various acaricides stress. For alterations in temperature, Hsp40 and α -TUB were the most suitable reference genes. About UV stress, EF1 α and α -TUB were the best choice, and for the different prey stress, β -ACT and α -TUB were best suited. In normal conditions, the β-ACT and α-TUB were the two of the highest stable reference genes to respond to all kinds of stresses. The current study provided a valuable foundation for the further analysis of gene expression in N. barkeri .